Plant and soil health in organic strawberry farms – Greater importance of fungal trophic modes and networks than α-diversity of the mycobiome - Siegieda, Dominika; Panek, Jacek; Frąc, Magdalena (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2023)
The mycobiome composition and health status of host plants are closely related. These relationships should be studied and recognized, as they may form the basis of future sustainable agriculture. The aim of this study was to select relevant biological indicators for monitoring soil microbial diversity by revealing characteristic differences between the mycobiomes of various soil compartments (bulk and rhizosphere) and plant niches (roots and shoots) from 13 healthy and diseased organic strawberry farms. The results of this study show that α-diversity of the mycobiome is less important in shaping plant health than fungal trophic mode composition. Healthy soil niches and roots contain less core taxa, but more differentially abundant taxa, than unhealthy ones. The results also suggest that plant health was shaped by more than just the most abundant fungal taxa, indicating that rare taxa should not be neglected in the analysis of mycobiome structure. We also demonstrate that fungal communities in the soil and plant niches from healthy strawberry farms create more stable and steady networks as compared to those from unhealthy farms. Finally, we show that the mycobiome roots-shoot axis is an important trait to consider in unhealthy plants from strawberry farms. [Display omitted] •We compared mycobiome of healthy and unhealthy strawberry soil and plant niches.•Healthy roots of strawberry had higher alpha-diversity of mycobiome than unhealthy.•Fungal networks of healthy soil and plant niches were more stable than unhealthy.•Rare microorganisms should not be neglected in such analyses.